Agile project management approach for engineering education: Eduscrum™ workshop - Filho, José Carlos Reston (2018)
EduScrum is an active collaborative education process that create an opportunity for students to make assignments according to a fixed rhythm. They plan and determine their own activities keeping track of their progress. The teacher “determines” the assignments, acting mainly as a coach and adviser. The event presents a path from teacher-driven education to student-driven and organized education. The teacher determines the Why and the What, the students determine the How. During the workshop a parallel will be drawn between scrum, education and applications in engineering education. The starting principles are the autonomy and authenticity of people. In eduScrum approach, students have to take responsibility for their own learning paths and work together independently. During the workshop, activities will be conducted to guide participants on the methods for team building and conducting the various stages of eduScrum. The expectation is that when passing through a guided experience, the participant understands in practice the various stages of the method. The objective is that at the end of the workshop, participants will be interested in trying out this student-centered methodology and looking for the necessary development of competences to apply eduScrum with their students.